Factors Affecting Customer Repurchase Intention: Case Study on Food Delivery Application - Ika Febrilia; Anisya Tiara Isnaini; Mohammad Rizan (LPPM Universitas Negeri Jakarta, 2023)
This study aimed to determine the direct effect of e-service quality, e-promotion, and perceived value variables on repurchase decision. As well as the indirect effect between e-service quality and e-promotion on repurchase decision through perceived value as an intervening variable. The research uses a quantitative approach and the data collection method uses a survey method with an instrument like a questionnaire. The object of research is 260 users of the McDelivery application who are domiciled in the JABODETABEK area, aged 17 years and over, who have seen/used the McDelivery online promotions McDelivery application to shop at least twice in the last six months. The data analysis technique used SPSS software and SEM analysis used LISREL software to process and analyze the research data. The results of the hypothesis test show that: (1) e-service quality affects repurchase decision; (2) e-promotion affects repurchase decision; (3) e-service quality affects repurchase decision through perceived value; (4) e-promotion affects repurchase decision through perceived value; (5) e-service quality affects perceived value; (6) e-promotion affects perceived value; (7) perceived value affects repurchase decision.